Assessment of job satisfaction, self-efficacy, and the level of professional burnout of primary and secondary school teachers in Poland during the COVID-19 pandemic - Bartosiewicz, Anna; Łuszczki, Edyta; Zaręba, Lech; Kuchciak, Maciej; Bobula, Gabriel; Dereń, Katarzyna; Król, Paweł (PeerJ, 2022)
Background The work of teachers during the COVID-19 pandemic created additional challenges and required them to go beyond conventional teaching methods, which in turn required teachers to be more resilient and caused stress and excessive workload. The aim of the study was to assess the level of occupational burnout, the sense of job satisfaction and the self-efficacy of primary and secondary school teachers working during the COVID-19 pandemic in Poland. Methods This is a cross-sectional descriptive study conducted among 412 teachers from randomly selected primary and secondary schools in the Podkarpacie region in Poland. The questionnaire contained socio-demographic data of the respondents and three standardized scales: The Scale of Job Satisfaction (SJS), General Self-Efficacy Scale (GSES) and Arbeitsbesorgenes Verhaltens und Erlebenmuster (AVEM). The Shapiro–Wilk, Kruskal–Wallis and Mann–Whitney U-test were used. Statistical analysis was performed with Statistica TIBCO 13.3 and R (version 3.6.1) software. Results The satisfaction with the work of the surveyed teachers was average in the job satisfaction scale. The vast majority of the surveyed teachers presented type B (overburdened risk type) of work-related behavior, and type A (overburdened risk type) in which the probability of burnout is very high. The feeling of self-effectiveness determines the level of job satisfaction and the level of professional burnout among the surveyed teachers. Job satisfaction had a statistically significant impact on the assessment of self-efficacy of the surveyed teachers (p < 0.0001). The types of work-related behavior have a statistically significant impact on the assessment of the teachers’ own effectiveness (p < 0.0001). Conclusion There is a close relationship between teachers’ level of self- efficacy, job satisfaction and, therefore it may predispose them to the occurrence of burnout syndrome in the future. Support for this professional group is needed. These findings may be important for education policy, teacher’s practice, and subsequent research. Ultimately, the study may provide some suggestions for methodological and educational strategies.
Keywords: Burnout; COVID-19; Job satisfaction; Self-efficacy; Teachers